Comparative effect of calcium channel blockers on the pancuronium neuromuscular blockers in Wistar rats - Ragavendra M.P; Rajendran K; Suresh R Rao; Sukesh Bhat; Hemasankar C (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Calcium channel blockers (CCB’s) are used in the treatment of cardiovascular disorders like hypertension, cardiac arrhythmias, angina, and other diseases. Several studies have reported that CCB’s inhibit neuromuscular transmission. In the in vitro studies, CCB’s along with standard skeletal muscle relaxants showed evidence of increasing the neuromuscular blockade effect. Neuromuscular blocking agents are used by the anaesthesiologists to improve the surgical procedures during surgery by the surgeons. Hence, in the current study, the comparative effects of verapamil, and benidipine on pancuronium neuromuscular blockers in Wistar rats were demonstrated. The 36 Wistar rats were divided into six groups, consisting of six rats in each group. The test drugs were injected intraperitoneally (IP) and neuromuscular blockade activity was observed over a period of one hour by inclined screen method and histological study of the skeletal muscles was done to compare the neuromuscular blocking effect. The comparative effect of the verapamil and benidipine indicates that it produces significant neuromuscular blocking activity and increase in the latency of hindlimb paralysis with benidipine suggest that benidipine is having more neuromuscular blocking activity when compared with verapamil.